Handbook of industrial drying - Mujumdar, Arun S. (CRC/Taylor & Francis, 2007)
Still the Most Complete, Up-To-Date, and Reliable Reference in the FieldDrying is a highly energy-intensive operation and is encountered in nearly all industrial sectors. With rising energy costs and consumer demands for higher quality dried products, it is increasingly important to be aware of the latest developments in industrial drying technologies. For two decades, Mujumdar's industry-standard Handbook of Industrial Drying has been the quintessential source of state-of-the-art information in the field, and this third edition is no exception.